FRET Monitoring of Intracellular Ketal Hydrolysis in Synthetic Nanoparticles. Issue 33 (25th July 2018) - Nuhn, Lutz; Van Herck, Simon; Best, Andreas; Deswarte, Kim; Kokkinopoulou, Maria; Lieberwirth, Ingo; Koynov, Kaloian; Lambrecht, Bart N.; De Geest, Bruno G.
Abstract: Degradable synthetic crosslinking is a versatile strategy to harness nanomaterials against disassembly in a complex physiological medium prompted by dilution effects or competitive interaction. In particular, chemical bonds such as ketals that are stable at physiological conditions but are cleaved in response to disease‐mediated or intracellular conditions (e.g., a mildly acidic pH) are of great relevance for biomedical applications. Despite the range of spectroscopic or chromatographic analyses methods that allow chemical degradation in solution to be assessed, it is much less straightforward to interrogate synthetic nanomaterials for their degradation state when located inside a living organism. We demonstrate a method based on FRET analysis to monitor intracellular disassembly of block‐copolymer‐derived nanoparticles engineered with a FRET couple on separate polymer chains, which after self‐assembly are covalently crosslinked with a pH‐sensitive ketal‐containing crosslinker. Abstract : Intracellular degradation of ketal‐crosslinked nanoparticles inside a living system was demonstrated by Förster resonance energy transfer (FRET) studies.